ANALISIS KEDISIPLINAN KINERJA GURU IPA TERPADU DI MTs THAMRIN YAHYA KECAMATAN RAMBAH HILIR TAHUN PEMBELAJARAN 2015/2016 - -, Karmina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
The aim of this study is to describe the discipline of integrated science teacherperformance MTs Thamrin Yahya districts Rambah Hilir. This type of research is descriptive.Population in this research is the principal, teachers and students integrated IPA. The samplingtechnique used for principals and teachers is total sampling technique. While the samplingtechnique to students is purposive sampling sampling with particular consideration The sample inthis research is the principal, integrated science teacher and eight students. The instrument usedwas a questionnaire that includes performance indicators disciplinary integrated science teacherJohn MTs Thamrin Rambah Hilir districts. The results showed that the average value of thepercentage of indicators disciplinary integrated science teacher performance MTs Thamrin YahyaRambah Hilir districts is 89,66%. It can be concluded that the criteria for disciplinary integratedscience teacher performance MTs Thamrin Yahya districts Rambah Hilir well.Keywords: Analysis , Discipline , Teacher Performance .